Development of an indirect ELISA for detecting Toxoplasma gondii IgG antibodies based on a recombinant TgIMP1 protein - Dong, Hongjie; Zhang, Junmei; Wang, Qi; Shen, Yanmei; Zhou, Beibei; Dai, Lisha; Zhu, Wenju; Sun, Hang; Xie, Xiaoman; Xie, Huanhuan; Xu, Chao; Zhao, Guihua; et al. (PLoS neglected tropical diseases, 2024)
Toxoplasma gondii ( T . gondii ) is widely spread around the world, which can cause serious harm to immunosuppressed patients. Currently, the commercial test kits are poor at assessing T . gondii infection and vaccine effectiveness, making an urgent need to exploit effective enzyme-linked immunosorbent assay with great performance to compensate for this deficiency. Here, the TgIMP1 recombinant protein was expressed in E . coli BL(21) cells. The TgIMP1 was purified with affinity chromatography and the reactivity was retained with anti-TgIMP1 antibodies. The TgIMP1 was then used to develop an indirect ELISA (IMP1-iELISA) and the reaction conditions of IMP1-iELISA were optimized. As a result, the cut-off value was determined to be 0.2833 by analyzing the OD 450nm values of forty T . gondii -negative sera. The coefficient of variation of 6 T . gondii -positive sera within and between runs were both less than 10%. The IMP1-iELISA was non-cross-reactive with the sera of cytomegalovirus, herpes virus, rubella virus, Cryptosporidium spp., Theileria spp., Neospora spp. and Plasmodium spp.. Furthermore, the sensitivity and specificity of IMP1-iELISA were 98.9% and 96.7%, respectively, based on testing 150 serum samples. The results suggest that this IMP1-iELISA is specific, sensitive, repeatable and can be applied to the detection of T. gondii infections in the medical and health industries.